SOSIALISASI DISCHARGE PLANNING PERAWAT RAWAT INAP DI RSUD KARAWANG - Dina Hartini; Grace Evelyn (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Discharge planning is a process that begins with the patient receiving health services followed by continuity of care both in the healing process and in maintaining health status until the patient feels ready to return to his environment, and is also an important part of implementing nursing care. With discharge planning can reduce the day / length of patient care, prevent recurrence, improve patient health conditions and reduce mortality and morbidity. This study aims to determine the relationship between knowledge and the implementation of discharge planning in the inpatient room of Dumai Hospital. The design of this study was cross sectional using the Chi square test. The sample is 96 implementing nurses. The sampling technique used is Proportional Stratified Random Sampling. The results of the study showed that most of the nurses were not good at carrying out discharge planning, namely 72.9%. most of the knowledge of nurses is not good at 89.6%.